The study on sports injury of coaches in boxing training environment - Kim, K.-W.; Kim, K.-J.; Chung, J.-W. (International Journal of Applied Sports Sciences, 2015)
The aim of this study was to investigate and analyze causes, times, regions, types, situations, first aid and treatment conditions of the injuries the boxing coaches. This study was conducted with a total of 80 subjects, who are currently active boxing coaches for middle school, high school, university, professional and national division. The tool used to investigate the nature of sports injuries of the boxing leaders based on the training environment was questionnaire, which is composed of 39 questions on age, sex, social background including leadership career, cause and time of injuries during training, type of region of injuries, injury regions based on type of training, first aid and treatment for injuries during training, and prevention of injuries. The questionnaire utilizes self-administered method. First, the form of training that exhibited highest injury rate during training was sparring, where attack type that most likely led to injuries was powerful hook. Second, the region of injury that exhibited highest injury rate during training was ligament injury, where upper limb area was more frequently observed than lower limb area. Third, most preferred emergency prevention method was ice packaging, and the most preferred hospital for treatment was western medicine based hospitals. Fourth, most of the coaches generally performed stretching before and after trainings. 16.25% of the coaches reported that they did not wear protection gears during training. In conclusion, this study that focused on causes, types, regions, first aid and treatment conditions of injuries for the coaches based on the training environment could aid in planning efficient measures for sports injuries of the boxing coaches and provide basic information to formulate treatment measures after injuries.